Comparison of modes of feedback on glide performance in swimming - Thow, J. L.; Naemi, R.; Sanders, R. H. (Journal of Sports Sciences, 2012)
The software product "GlideCoach" was recently developed to give quantitative and qualitative feedback on the glide performance of a swimmer (Naemi & Sanders, 200821. Naemi , R. and Sanders , R. 2008 . A "hydro-kinematic" method of measuring glide efficiency of a human swimmer . Journal of Biomechanical Engineering , 130 ( 6 ): 9-16 . This study compared the effect of feedback on glide performance from GlideCoach with video and verbal feedback. Nineteen elite swimmers were randomly assigned to one of three groups: Group 1 and 2 included six swimmers and Group 3 included seven swimmers. All participants performed ten dives in each of five sessions. Each group received one of three forms of feedback (video, video and verbal, and GlideCoach and verbal) for four sessions. In the fifth, retest session, performed 4 weeks after the fourth session, all groups received GlideCoach and verbal feedback only. This enabled the analysis of GlideCoach and verbal feedback on performance of the groups that had not yet received this feedback and assessment of the retention ability for the group that had. Feedback resulted in all groups recording an improvement, as indicated by effect sizes, for average velocity, glide factor (related to resistive drag), and initial velocity (P < 0.05). The improvement following the GlideCoach and verbal feedback was greater than that of the two other feedback methods for all variables of interest (P < 0.05), with effect sizes ranging from 1.0 to 2.5, compared with values less than 0.6 for the other feedback methods. We conclude that GlideCoach feedback is effective in improving glide performance.